PENAMBAHAN BROKOLI (Brassica oleraceae var. italica) PADA PEMBUATAN NUGGET IKAN LELE (Clarias gariepinus) UNTUK MENINGKATKAN KANDUNGAN SERAT KASAR DAN KALIUM - Clinton Umbu Baru Lalu Hangga; Ilminingtyas Dyah; Diah Kartikawati (Jurnal Agrifoodtech, 2026)
Nugget is a high protein frozen food. Catfish is one of the raw materials that can be used to make nugget Catfish contains high protein, tastes good, has a soft texture and is relatively cheap. To increase the nutritional content, vegetables are added in the processing. Broccoli is one of the vegetables that can be added in making nuggets because contains high fiber and potassium. The purpose of this study was to determine the effect of adding broccoli with different concentrations on the crude fiber, potassium and organoleptic values of catfish nuggets. The research design used was a completely randomized design with 4 treatments, each with 3 replications. The treatment in this study was based on the concentration of broccoli added, namely B0 (0%), B1 (25%), B2 (50%) and B3 (75%). Parameters observed were crude fiber, potassium, and organoleptic value of catfish nuggets. The results showed that the addition of broccoli at various concentrations had a significant effect (P<0.05) on crude fiber, and potassium value but had no significant effect on organoleptic values. The most preferred nuggets with the addition of broccoli was treatment B1 (25%). The addition of broccoli in the processing of catfish nuggets can increase crude fiber and potassium.